Non-perennial Mediterranean rivers in Europe: Status, pressures, and challenges for research and management - Skoulikidis, Nikolaos T (2017)
Non-perennial rivers and streams (NPRS) cover > 50% of the global river network. They are particularly predominant in Mediterranean Europe as a result of dry climate conditions, climate change and land use development. Historically, both scientists and policy makers underestimated the importance of NRPS for nature and humans alike, mainly because they have been considered as systems of low ecological and economic value. During the past decades, diminishing water resources have increased the spatial and temporal extent of artificial NPRS as well as their exposure to multiple stressors, which threatening their ecological integrity, biodiversity and ecosystem services. In this paper, we provide a comprehensive overview of the structural and functional characteristics of NPRS in the European Mediterranean, and discuss gaps and problems in their management, concerning their typology, ecological assessment, legislative and policy protection, and incorporation in River Basin Management Plans. Because NPRS comprise highly unstable ecosystems, with strong and often unpredictable temporal and spatial variability – at least as far as it is possible to assess – we outline the future research needs required to better understand, manage and conserve them as highly valuable and sensitive ecosystems. Efficient collaborative activities among multidisciplinary research groups aiming to create innovative knowledge, water managers and policy makers are urgently needed in order to establish an appropriate methodological and legislative background. The incorporation of NPRS in EU-Med River Basin Management Plans in combination with the application of ecological flows is a first step towards enhancing NPRS management and conservation in order to effectively safeguard these highly valuable albeit threatened ecosystems.